2006
DOI: 10.1017/s0031182006000229
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of an asparaginyl proteinase (legumain) from the parasitic nematode, Haemonchus contortus

Abstract: Asparaginyl proteinases (or legumains) are a recently identified, novel class of cysteine proteinase which specifically hydrolyse peptide bonds after asparagine residues. Legumains have been implicated in the activation of cysteine proteases, particularly cathepsin B-like proteinases which are thought to help degrade the bloodmeal in blood-feeding helminths such as schistosomes, hookworms and other nematode species. An EST sequence representing a full-length legumain was identified from the Haemonchus contortu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 30 publications
1
28
0
Order By: Relevance
“…We postulate that Blastocystis legumain possesses multiple functions and plays important roles at the cell surface and within acidic compartments. Legumains are generally located within lysosomes of mammalian cells and vacuoles of plant cells but have been reported to localize to the cell surface of metastatic tumors (17) and on the microvillar surfaces of helminth intestinal cells (25). Surface legumains were suggested to activate local zymogens that may aid tumor invasion or participate in helminth alimentary digestion of host proteins.…”
Section: Discussionmentioning
confidence: 99%
“…We postulate that Blastocystis legumain possesses multiple functions and plays important roles at the cell surface and within acidic compartments. Legumains are generally located within lysosomes of mammalian cells and vacuoles of plant cells but have been reported to localize to the cell surface of metastatic tumors (17) and on the microvillar surfaces of helminth intestinal cells (25). Surface legumains were suggested to activate local zymogens that may aid tumor invasion or participate in helminth alimentary digestion of host proteins.…”
Section: Discussionmentioning
confidence: 99%
“…However, the fact that HlLgm expression was most abundant in the midgut, and furthermore that endogenous HlLgm expression was up regulated in partially fed ticks clearly suggest some critical relationship between HlLgm and blood-meal digestion. Legumains in the parasitic nematode Haemonchus contortus (Oliver et al, 2006) andS. mansoni (El Meanawy et al, 1990) have been reported to be expressed in the gut epithelial cells of the parasites.…”
Section: Discussionmentioning
confidence: 99%
“…The pH optima of the legumains of blood-feeding helminth parasites S. mansoni and H. contortus are pH 6.8 and pH 7, respectively (Dalton, et al, 1995;Oliver et al, 2006). In contrast, mammalian and plant legumains have been shown to be active in acidic environment and are very labile at neutral pH (Hara-Nishimura et al, 1991;Ishii, 1994;Chen et al, 1997, Chen et al, 1998a.…”
Section: Article In Pressmentioning
confidence: 99%
“…22.34), also known as asparaginyl endopeptidase, is a novel class of cysteine protease, which was identified originally in leguminous plants, hence the name legumain [1], and later first identified in animals in the human blood fluke Schistosoma mansoni [2]. It has since been found in mammals [3,4], in the parasitic protozoan Trichomonas vaginalis [5], in the parasitic nematodes Toxocara canis and Brugia malayi [6], and Haemonchus contortus [7], and in the parasitic arthropods Ixodes ricinus [8], Fasciola gigantica [9] and Haemaphysalis longicornis [10]. However, little information regarding legumains is available in the lower chordates.…”
Section: Introductionmentioning
confidence: 99%